MODEL PEMBELAJARAN SCL GROOVING BERBASIS TEKNOLOGI INFORMASI DI SEKOLAH DASAR - Endi Sutrisna; Baehaki; Sakti Handayani; Dethia HS Suci Nurani; Siti Laela (STKIP Subang, 2026)
The paradigm shift from teacher-centered to student-centered learning demands that teachers continuously innovate to create effective, engaging, and up-to-date learning experiences. This article aims to describe and analyze the innovation of the